2012
DOI: 10.1080/01621459.2012.699793
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution When Classifying Noisy Data Involving Transformations

Abstract: In the present study, we consider the problem of classifying spatial data distorted by a linear transformation or convolution and contaminated by additive random noise. In this setting, we show that classifier performance can be improved if we carefully invert the data before the classifier is applied. However, the inverse transformation is not constructed so as to recover the original signal, and in fact, we show that taking the latter approach is generally inadvisable. We introduce a fully data-driven proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Finally, we note the work by Carroll and Hall (1988); Stefanski and Carroll (1990); Zhang (1990); Fan (1991); Fan and Koo (2002); Hall et al (2007); Carroll et al (2012); Delaigle and Hall (2014), among others, who considered kernel estimators. Their idea is motivated by (1) after taking the Fourier transform of the corresponding convolution of densities, then solving for the unknown mixing density using kernel approximations for the Fourier transform of the true marginal density.…”
Section: Connections With Previous Workmentioning
confidence: 87%
“…Finally, we note the work by Carroll and Hall (1988); Stefanski and Carroll (1990); Zhang (1990); Fan (1991); Fan and Koo (2002); Hall et al (2007); Carroll et al (2012); Delaigle and Hall (2014), among others, who considered kernel estimators. Their idea is motivated by (1) after taking the Fourier transform of the corresponding convolution of densities, then solving for the unknown mixing density using kernel approximations for the Fourier transform of the true marginal density.…”
Section: Connections With Previous Workmentioning
confidence: 87%
“…So there is a lot of interest in knowing whether the two types of clouds are different. The data have been previously described in Carroll et al (2012) and discussed recently in Serban et al (2013) and Xun et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The data are described in detail by Carroll et al (2012), and the estimation of spectral backscatter uses the algorithm of Warren et al (2008, 2009), but applied to the observed data rather than the deconvolved data. Our main goal is to estimate the probability of high spectral backscatter at different wavelengths.…”
Section: Discussionmentioning
confidence: 99%